Biomass constituents' interactions with coal during co-firing. (February 2019) - Oladejo, Jumoke; Shi, Kaiqi; Meng, Yang; Adegbite, Stephen; Wu, Tao
Abstract: The importance of biomass in the emerging low carbon economy remains quite crucial especially relating to the co-firing of coal and biomass due to the improvements in thermal properties and its influence on reactivity, burnout and flame stability. In this research, the combustion profile of coal and biomass blends, coal and low temperature biomass ash blends and coal and demineralized biomass blends were studied using thermogravimetric analysis. The results established the presence of both mechanism of synergy in the fuel blends during co-firing. This was substantiated by significant decrease in peak, burnout temperature as well as reduction in activation energy, demonstrating non-additive interaction between the biomass and coal sample. Further deductions reveal a degree of overlap in the function of catalytic and non-catalytic synergy mechanisms in the biomass blends due to competitive reactions among the catalyzing AAEMs and the hydrogen contributing organic constituents of biomass with coal. Finally, this study further establishes a higher degree of catalytic synergy in potassium rich oat straw in comparison to calcium rich gumwood.